CD4+, CD8+ AND CD19+ Cells at Individuals with Dyslipidemia - Pereira de Moura, Jose (2013)
Introduction: The past decade has witnessed an increasing recognition that inflammatory mechanisms play a central role in the pathogenesis of atherosclerosis and its complications. Recently, attention was focused on the potential role of plasma markers of inflammation as risk predictors among those at risk for cardiovascular events. Of these potential markers, C-reactive protein (CRP), IL6, metalloproteinases, ICAM, VCAM and other molecules, have been extensively studied. On the other hand, to our knowledge, there are only a few studies on the role of inflammatory cells, like T and B lymphocytes in the atherosclerosis.Material and Methods: By Flow Cytrometry analysis we have determined on dyslipidemic people and on a control group, the percentage of some peripheral inflammatory cells, like CD3+, CD4+, CD8+, CD19+, CD56+, CD56CD8+, DN, CD25+, CD26+, CD25CD3+, CD26CD3+, CD25CD26CD3+, CCR5+, CCR5CD3+, CCR5CD4+, HLADR+, HLADRCD4+, HLADRCD8h+, HLADRCD8low+, HLADRCD8+, CD95+, CD95CD95L+, CD3CD95+, CD3CD95L+, CD62L+, CD3CD62L+, CD69+, CD69CD3+ e CD69CD4+.Results: In the present study we have particularly studied the percentage of CD4+, CD8+ and CD19+ cells. The CD4+ cells have been significantly reduced in the people with dyslipidemia.Discussion: We do not know the peripheral numbers of the subtype Th1 and Th2, neither the percentage of CD4+CD25+ cells (regulatory T cells). We have not find any differences on the percentage from the CD8+ and CD19+ cells.Conclusions: In spite of the identified limitations resulting from the small-sized samples, it was possible to show a reduction of some molecules after application of acetylsalicylic acid.